2017
DOI: 10.1177/0954008317731504
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a carborane-containing monofunctional imide monomer as a modifier for imide oligomer

Abstract: A novel carborane-containing imide monomer (CB-PEPA) was synthesized and used as a modifier for phenylethynyl-terminated imide oligomer (PI-mPDA) to study the effect on the performance of the oligomers and thermosetting polyimide materials. The curing behavior of the blends of CB-PEPA and PI-mPDA was investigated by differential scanning calorimetry (DSC). It showed that CB-PEPA had a melting point at 183°C. Nonisothermal DSC showed that imide monomer had higher activation energy than that of bifunctional imid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…[26] A carborane-containing imide monomer was synthesized as well and used as a modifier to improve the thermal stability and T g of PI. [27] Cheng et al also reported a series of carborane-containing copolymer PIs, which showed that the T g , thermal and thermo-oxidative stability of the resulting PIs were improved by the addition of an acetylenic monomer containing carborane; and the thermoset derived from the pure carborane-containing acetylenic monomer exhibited the highest T g value of 455 °C. [7] However, all these PIs are obtained via copolymerization of imide oligomers with reactive monomer containing carborane, which has limited improvement in T g and thermal stability.…”
mentioning
confidence: 99%
“…[26] A carborane-containing imide monomer was synthesized as well and used as a modifier to improve the thermal stability and T g of PI. [27] Cheng et al also reported a series of carborane-containing copolymer PIs, which showed that the T g , thermal and thermo-oxidative stability of the resulting PIs were improved by the addition of an acetylenic monomer containing carborane; and the thermoset derived from the pure carborane-containing acetylenic monomer exhibited the highest T g value of 455 °C. [7] However, all these PIs are obtained via copolymerization of imide oligomers with reactive monomer containing carborane, which has limited improvement in T g and thermal stability.…”
mentioning
confidence: 99%
“…Obviously, as shown in Figure 7, the carborane-containing monomer CB-MI showed the highest thermal stability, and is well in agreement with the results previously reported for carborane-containing imide monomer. 25,26 The char yield at 600°C of cured CB-MI reached 85.1%. It could be attributed to the presence of a passivation layer with oxidized carborane formed on the sample surface to prevent further erosion.…”
Section: Methodsmentioning
confidence: 96%
“…Further, the blend resins exhibit lower T 5 and T 10 together with higher char yield at 600°C than the cured BDM due to the introduction of carborane into the system, and it is well in agreement with the previously reported carborane-containing polyimides. 25,26 For example, the T 5 of BMI-CB20 decreased by around 26°C compared to BDM, while the corresponding char yield at 600°C increased from 56.0% to 69.5%. The results indicated that the incorporation of carborane group into a polymer could significantly enhance the thermal stability.…”
Section: Methodsmentioning
confidence: 98%
“…Due to their outstanding thermal stability, icosahedral carboranes, a class of carbon-containing boron-cluster compounds, were also utilized to prepare reactive diluents. [39] Chen et al [40] synthesized a carborane-containing imide oligomer (CB-PEPA). It was found that CB-PEPA not only improves melting processability, but also improves the thermal stability and mechanical properties of the cured resins.…”
Section: Introductionmentioning
confidence: 99%